20th century Britain
1 online resource (xxi, 380 pages)
Keywords: "20th Century Britain provides an authoritative and accessible survey of contemporary research on economic activity, society, political development and culture. Written by leading academics, it examines recent advances in scholarship and gives a grounding in established approaches and topics. This collection provides an essential guide to current academic thinking on the most important elements of twentieth-century British history and is a useful tool for all students and scholars interested in modern Britain"--